PROFIL PERESEPAN OBAT GENERIK DIAPOTEK X KABUPATEN INDRAMAYU PERIODE JANUARI – MARET TAHUN 2019 - Diana Fitri Dama Yanti; Marini Marini (STIKes Muhammadiyah Kuningan, 2019)
Many people still do not know about generics and consider generic drugs as quality drugs, less useful properties. Besides that, some doctors prefer to prescribe branded generic drugs rather than generic drugs. In accordance with Permenkes RI No.HK.02.02 / Menkes / 068/2010 concerning the obligation to use generic drugs for the fasility of government health services, This study aims to determine the percentage of prescription and replacement of generic drugs by taking prescription data in Pharmacy X of Indramayu Regency during January-March 2019 then grouped into generic drugs, branded generic drugs, others, replacement of generic drugs to branded generic drugs and replacement of branded generic drugs to generics then the percentage is calculated and the data are generated, the percentage of prescription for generic drugs 41, 52%, branded generic drugs 44.91%, replacement of generic drugs for branded generic drugs 18.36%, replacement of generic drugs for generic drugs 3.77%. So it shows that indeed the lack of information, counseling, understanding, and promotion makes the public and medical practitioners still consider generic drugs to be of poor quality.